Analisis Pelatihan dan Pengembangan Sumber Daya Manusia Aparatur Sipil Negara di Kantor Camat Gunungsitoli Barat - Martalena Harefa; Sukaaro Waruwu; Yamolala Zega; Eliagus Telaumbanua (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to find out and analyze the training and resource development of State Civil Apparatus ASN at the West Gunungsitoli Sub-district office for inhibiting and supporting factors for the implementation of training and resource development of the State Civil Apparatus at the West Gunungsitoli Sub-district office. . The method used in this study is a qualitative research method with a descriptive approach. The theory used is a management theory that focuses on the theory of resource management of the State Civil Apparatus. The results of this study show that the training and development carried out at the West Gunungsitoli Sub-district Office is leadership, administration and socialization training. The factors that hinder training and development are : budget constraints, time constraints, lack of involvement and skills gaps. Meanwhile, those who are supporters in training and development are training materials that are considered appropriate and interesting as well as resource persons who are able to share interesting experiences and knowledge.